Dealing with uncertainty and risk in the design of deep and high stress mining excavations - Joughin, W.C. (Deep Mining 2017: Proceedings of the Eighth International Conference on Deep and High Stress Mining, 2017)
A method for risk-based design under high stress conditions is described in this paper. Probabilistic methods of analysis are applied to stress modelling to determine the probability of exceeding a given depth of failure. Suggestions are provided for dealing with geotechnical uncertainty. The understanding of aleatory variability can be improved by collecting more data and improving the quality of data through training and quality control. Stress and model uncertainty remain a challenge in geotechnical engineering. Some degree of subjective engineering judgement will therefore always be required in geotechnical design. An economic risk model is used to determine the frequency and severity of the consequences of stress damage. The cost of rehabilitation of tunnels and the financial losses due to lost production are assessed using the model. A typical risk matrix is used to evaluate the level of risk. Different types of excavations have different risk profiles based on the potential impact on production. The design engineer can use the model to determine design criteria for stress damage. The risk can be mitigated through improved support or by changing the mining layout. These measures both have financial implications and the economic risk model is useful for decision making. A brief discussion on risk-based design criteria for rockbursts is also included.